2016
DOI: 10.3390/ijerph13111057
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Exposures to Ionizing Radiation: Carcinogenic Considerations

Abstract: Children are at a greater risk than adults of developing cancer after being exposed to ionizing radiation. Because of their developing bodies and long life expectancy post-exposure, children require specific attention in the aftermath of nuclear accidents and when radiation is used for diagnosis or treatment purposes. In this review, we discuss the carcinogenic potential of pediatric exposures to ionizing radiation from accidental, diagnostic, and therapeutic modalities. Particular emphasis is given to leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 97 publications
(118 reference statements)
0
108
0
2
Order By: Relevance
“…Much like lead, chlordane is a developmental immunotoxicant that has in utero effects at doses that have no effect on the immune system of the mother [130]. Kutanzi et al, in a review of pediatric exposures to ionizing radiation highlighted the potential adverse health outcomes (e.g., cancers) for children following exposures to low concentration of accidental and technological radiation, implying care when treating with diagnostic radiation considering the sensitivities of children and the potential role of genetic differences [142]. …”
Section: Resultsmentioning
confidence: 99%
“…Much like lead, chlordane is a developmental immunotoxicant that has in utero effects at doses that have no effect on the immune system of the mother [130]. Kutanzi et al, in a review of pediatric exposures to ionizing radiation highlighted the potential adverse health outcomes (e.g., cancers) for children following exposures to low concentration of accidental and technological radiation, implying care when treating with diagnostic radiation considering the sensitivities of children and the potential role of genetic differences [142]. …”
Section: Resultsmentioning
confidence: 99%
“…A review of Gianicolo et al showed that currently there are methodological limits in the available studies and that accurate risk estimation in adolescents and children undergoing to exposition to ionizing radiations is not well estimated [27]. One of the most recent reviews by Kutanzi et al highlights the need of minimizing the negative health effects of pediatric exposure to ionizing radiations [28]. On these bases and given that the most frequent arrhythmias in pediatric population are supraventricular tachycardias [3], which are most often not fatal conditions, it seems a reasonable approach a further decrease of radiation exposure [19].…”
Section: Discussionmentioning
confidence: 99%
“…Only a marginal non-significant increase in a specific type of lymphoma (i.e., non-Hodgins) was observed in areas with the higher radon concentrations. The third article on radiation is a review article by Kutanzi et al This article focuses on pediatric exposures to ionizing accidental, technological and diagnostic radiation and the potential for carcinogenic outcomes given existing radiosensitivities [6]. The authors emphasize that the role of genetic sensitivities during and following radiation exposures needs to be further explored [6,7].…”
Section: Articles In This Special Issuementioning
confidence: 99%